2015
DOI: 10.1371/journal.pone.0126725
|View full text |Cite
|
Sign up to set email alerts
|

Corosolic Acid Inhibits Hepatocellular Carcinoma Cell Migration by Targeting the VEGFR2/Src/FAK Pathway

Abstract: Inhibition of VEGFR2 activity has been proposed as an important strategy for the clinical treatment of hepatocellular carcinoma (HCC). In this study, we identified corosolic acid (CA), which exists in the root of Actinidia chinensis, as having a significant anti-cancer effect on HCC cells. We found that CA inhibits VEGFR2 kinase activity by directly interacting with the ATP binding pocket. CA down-regulates the VEGFR2/Src/FAK/cdc42 axis, subsequently decreasing F-actin formation and migratory activity in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…The principal compounds are triterpenes, which exhibit remarkable anticancer effects in HCC [79]. Other compounds have also shown cytotoxic activity including the phenolic constituents and isomeric flavonoids [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The principal compounds are triterpenes, which exhibit remarkable anticancer effects in HCC [79]. Other compounds have also shown cytotoxic activity including the phenolic constituents and isomeric flavonoids [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Corosolic acid, a natural triterpenoid compound derived from banaba leaves and apples, has been shown to have anti-tumor effects on a variety of tumor models, such as glioblastoma 118 , prostate cancer 119,120 , retinoblastoma 121 , renal carcinoma 122 , gastric cancer 123 , breast cancer 124 , liver cancer 125,126 , colon cancer 127 , lung adenocarcinoma 128 , cervix adenocarcinoma 129 , osteosarcoma 130,131 . Similar to curcumin and resveratrol, CA is a potent STAT3 inhibitor, suppressing cell growth of ovarian cancer and glioblastoma by abrogating STAT3 activity 118,132 .…”
Section: Corosolic Acidmentioning
confidence: 99%
“…An in vivo mouse model showed that Corosolic acid exhibited a significant effect on tumor growth with a relative low dose. Ku et al [34] further demonstrated that the combination of Corosolic acid and sorafenib can synergistically affect tumor growth with a wide range of concentrations.…”
Section: Clinical Experience With Inhibitors Of Src Signalingmentioning
confidence: 99%